Developmental Insights into Breast Cancer Intratumoral Heterogeneity - Zhang, Mei (Trends Cancer, 2015)
Breast cancer is no longer considered a single disease, but instead is made up of multiple subtypes with genetically and most likely epigenetically heterogeneous tumors composed of numerous clones. Both the hierarchical cancer stem cell and clonal evolution models have been invoked to help explain this intratumoral heterogeneity. Several recent studies have helped define the functional interactions among the different cellular subpopulations necessary for the evolution of this complex ecosystem. These interactions involve paracrine interactions that include locally acting Wnt family members, reminiscent of the signaling pathways important for normal mammary gland development and stem cell self-renewal. In this review, we discuss the interactions among various cell populations in both normal and tumor tissues. A better understanding of these interactions, especially in the metastatic setting, will be important for the development of improved combinatorial therapies designed to prevent relapse and to ultimately decrease mortality.